Diversity and community assembly mechanisms of soil methanotrophs in typical ecotypes of the Mitika alpine wetland in northern Xizang - Cao, Pengxi; Wang, Yuyan; Wang, Zhe; Cao, Liang; Li, Hairong; Ma, Hongmei; La, Qiong (Frontiers in Microbiology, 2025)
The Mitika alpine wetland is a globally important wetland on the Qinghai-Xizang Plateau, which serves as a vital carbon reservoir on Earth’s surface. However, the seasonal variation characteristics of its soil methanotrophs communities remain poorly understood. To deepen our understanding of the role of this biome in geochemical cycles, we selected three typical ecosystems from the Mitika wetland in northern Xizang: alpine grassland, swamp meadow, and fen. Surface soil samples were collected across spring, summer, autumn, and winter seasons. Using high-throughput sequencing, we analyzed methanotrophs diversity, community structure, and responses to environmental factors. The dominant phyla were α-Proteobacteria (Type II aerobic methanotrophs), candidate_division_NC10, and unclassified bacteria. At the genus level, Methylocystis, Methylococcus, and Methylocapsa were the primary taxa. Neutral model analysis indicated that random processes dominate community assembly, with winter communities better fitting the neutral model and exhibiting lower diffusion constraints. Among environmental factors, pH, Total Nitrogen (TN), Electrical Conductivity (EC), Salt (Salt), and Water Content (WC) showed significant correlations with certain methanotrophs groups. Structural equation modeling further revealed that fundamental soil physicochemical factors exert a significant positive influence on alpha diversity. Our findings reveal the seasonal dynamics and ecosystem differences of methanotrophs communities in the Mitika alpine wetland, thus contributing to a more thorough understanding of carbon cycling functions in alpine wetlands.